2017
DOI: 10.21037/jss.2017.09.05
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of lumbar posterior stabilization and fusion to vertebral bone density in stabilized and adjacent segments by using Hounsfield unit

Abstract: Decrease in the bone density of the adjacent segment vertebral bodies may be one of the major predisposing factors for adjacent segment disease (ASD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 26 publications
0
19
0
1
Order By: Relevance
“…In the USA, by age 60 years, half of Caucasian women have osteopenia . The current standard of BMD assessment, DXA, is based on a person's BMD T‐score at the hip and lumbar spine, according to the World Health Organization diagnostic classification . Fundamental differences exist between DXA and CT vertebral densitometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the USA, by age 60 years, half of Caucasian women have osteopenia . The current standard of BMD assessment, DXA, is based on a person's BMD T‐score at the hip and lumbar spine, according to the World Health Organization diagnostic classification . Fundamental differences exist between DXA and CT vertebral densitometry.…”
Section: Discussionmentioning
confidence: 99%
“…The CT software reported the average CT attenuation of the ROI in HU. These methods have been evaluated and shown to produce reliable results . We measured thoracic vertebra (Th) 12, lumbar vertebrae (L) 1–5, and sacrum vertebra (S) 1.…”
Section: Methodsmentioning
confidence: 99%
“…Hounsfield units (HUs) on CT as a proxy for BMD have been shown to correlate with DXA values. 18,[22][23][24] Studies have demonstrated a correlation between HUs and DXA scores when comparing osteoporotic and non-osteoporotic patients, 23,25 with a positive correlation between the T-score on DXA and the HU value on spinal CT. 18,25 However, these studies have focused on degenerative conditions of the lumbar spine, and it is unclear if HUs reliably reflect the BMD of the LT vertebrae, the often-chosen UIV level in ASD surgery. We evaluated whether the HU values at the UIV, UIV+1, and UIV+2 (2 levels above the UIV) were associated with PJK in ASD patients over 50 years old.…”
mentioning
confidence: 99%
“…6,21 BMD is normally evaluated using dual-energy x-ray absorptiometry (DXA). 18,22 However, DXA scans in the lumbar spine may not always be accurate given the amount of degeneration obscuring the true values, and spinal instrumentation can obfuscate interpretation. 18,22 Moreover, not all patients obtain a preoperative DXA scan.…”
mentioning
confidence: 99%
See 1 more Smart Citation